Effects of Capsules Containing Waste Oils on the Mechanical Properties of Hot Mix Asphalt: Experimental Approach - Ozdemir, Ahmet Munir; Yilmaz, Mehmet; Yalcin, Erkut; Kok, B. Vural; Norambuena-Contreras, Jose; Garcia, Alvaro (Asce-Amer Soc Civil Engineers, 2021)
Self-healing asphalt with encapsulated rejuvenators is a promising technology to improve the service life of asphalt pavements. Broken capsules reduce the viscosity of aged bitumen due to rejuvenator diffusion, sealing open microcracks at an early stage. Several waste oils have been used as low-cost rejuvenating agents in capsule production to reduce costs and enable the environmental benefits of this technology. This study aims to evaluate the effects of capsules containing waste vegetable oil (WVO) and waste mineral oil (WMO) on the mechanical properties of hot mix asphalt (HMA). Four capsule content amounts (0.25%, 0.50%, 0.70%, and 1.00% by weight) were included in HMA samples, which were evaluated through experimental standard tests such as stiffness modulus, indirect tensile strength, fatigue life, and moisture-induced damage. The results revealed that an increase in capsule content led to less rigidity and strength against permanent deformation and fatigue. It was also determined that the strength against permanent deformation of mixtures with WMO capsules increased more than that of mixtures with WVO capsules. Another finding is that the optimum capsule content ratio in asphalt mixtures is 0.50% by weight for both capsule types.
Keywords: Hot mix asphalt (HMA); Mechanical properties; Encapsulated rejuvenators; Waste vegetable oil (WVO); Waste mineral oil (WMO)